Fat digestibility in meat products: influence of food structure and gastrointestinal conditions. (4th July 2019) - Asensio-Grau, Andrea; Calvo-Lerma, Joaquim; Heredia, Ana; Andrés, Ana
Abstract: Digestibility of macronutrients depends on the food matrix structure as well as on gastrointestinal conditions, especially in patients with exocrine pancreatic insufficiency. In this situation, an oral enzyme supplementation that promotes nutrient hydrolysis is needed. In this context, in the present study, a static in vitro digestion model was used to assess the lipid digestibility of different meat products (processed and fresh), different intestinal conditions of pH (6 or 7), bile concentration (1 or 10 mM) and doses of the enzyme supplement (1000–4000 lipase units/g fat). Results showed that processed (unstructured) meats had better matrix degradation during digestion and reached higher values of lipolysis extents (total free fatty acids/g fat) than the natural meat matrices with a statistically significant association ( p < .001). Regarding the intestinal medium, pH of 7 and bile concentration of 10 mM contribute to higher matrix degradation and thus, to a higher lipolysis ( p < .001).